The Research on Intelligent Measurement Terminal of Water-Saving Irrigation Based on RN2026 Microcontroller. (20th April 2023) - Guo, Runzhou; Liu, Shujie; Liu, Xiaoxiao; Liu, Beilei; Gu, Zhanlei
Abstract : Water-saving irrigation technology has been studied for many years, but due to insufficient investment in research and development of irrigation equipment, it cannot be effectively promoted and applied. In order to improve the water use efficiency of farmland irrigation, the automatic monitoring of groundwater level change, soil moisture change, and crop seasonal growth status is realized in the ditch or pump well irrigation area. An intelligent measuring terminal for water-saving irrigation based on RN2026 microcontroller is developed. The terminal uses the coefficient of "water conversion by electricity" to automatically convert the water consumption of farmers and uses the price mechanism of water rights to affect farmers' water conservation. In combination with changes in groundwater level, crop evapotranspiration, and dynamic changes in soil moisture, precision irrigation strategies are automatically generated to guide farmers to use water rationally. Through the function and performance experiments, the results show that the error of the coefficient of "water conversion by electricity" is less than 1%, the error of electric energy measurement is less than 0.5%, the estimated value of average water use right per unit arable area is consistent with the actual value, and the predicted value of daily average soil moisture change is consistent with the measured value. The equipment has strong adaptability to the environment, high measurement accuracy, strong data processing ability, low cost, and other characteristics. It meets the requirements of water-saving irrigation technology in practical applications and has good promotion and application value.